Feasibility of three-dimensional CT reconstruction in assessing mandibular fractures - Victor Nogueira Moura; Emerson Nogueira; Ewerton Daniel Rocha Rodrigues; Caio Gonçalves Silva; Ricardo José de Holanda Vasconcellos (Universidade Estadual de Campinas, 2021)
Aim: Evaluation of the reliability of 3D computed tomography (3D-CT) in the diagnosis of mandibular fractures. Methods: A cross-sectional, quantitative and qualitative study was carried out, through the application of a questionnaire for 70 professionals in the area of Oral and Maxillofacial Surgery and Radiology. 3D-CT images of mandibular fractures were delivered to the interviewees along with a questionnaire. Participants answered about the number of traces, the region and the type of fracture. The correct diagnosis, that is, the expected answer, was based on the reports of a specialist in oral and maxillofacial radiology after viewing the images in the axial, sagittal and coronal sections. The resulting data from the interviewees was compared with the expected answer and then, the data was analyzed statistically. Results: In the sample 56.9% were between 22 and 30 years old, 52.8% were oral and maxillofacial surgeons (OMF), 34.7% were residents in OMF surgery and 12.5% OMF radiologists. Each professional answered 15 questions (related to five patients) and 50.8% of the total of these was answered correctly. Specialists in Oral and Maxillofacial Surgery and Traumatology correctly answered 53.9%. Interviewees with experience between 6 and 10 years correctly answered 58.2%. In identifying fracture traces, 46.1% of the questions were answered correctly. In terms of location, 5.6% of interviewees answered wrongly while 14.2% answered wrongly regarding classification. Conclusion: 3D computed tomography did not prove to be a reliable image for diagnosing mandibular fractures when used alone. This made necessary an association with axial, sagittal and coronal tomographic sections.